2016
DOI: 10.1080/09168451.2015.1091713
|View full text |Cite
|
Sign up to set email alerts
|

Enteric lactoferrin attenuates the development of high-fat and high-cholesterol diet-induced hypercholesterolemia and atherosclerosis in Microminipigs

Abstract: Previously, we found that enteric lactoferrin (eLF) could reduce the visceral fat accumulation known to associate strongly with metabolic syndrome symptoms and consequently with an increased risk of atherosclerosis. In this study, the atherosclerosis-preventive potential of LF was assessed in a high-fat and high-cholesterol diet (HFCD)-induced hypercholesterolemia and atherosclerosis model using Microminipig™. Eight-week orally administered eLF remarkably reduced the HFCD-induced serum total and low-density li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Moreover, significant additive interactions between famine exposure and the high-fat and high-salt dietary pattern on the risk of diabetes and hypercholesterolaemia were found. Morishita et al reported that highfat diet behaviour could form atherosclerotic plaque and block blood vessels by damaging vascular endothelium and, thereafter, contribute to hypertension and other cardiovascular and cerebrovascular diseases by lumen narrowing (36) . In addition, high-salt diets can promote body fluid volume expansion, adrenal cortical production and release of sodium pump inhibitor increasing through inhibiting the cell membrane Na + 2K + 2ATP enzyme activity, which could contribute to blood pressure elevation and dyslipidaemia (37) .…”
Section: Main Findingsmentioning
confidence: 99%
“…Moreover, significant additive interactions between famine exposure and the high-fat and high-salt dietary pattern on the risk of diabetes and hypercholesterolaemia were found. Morishita et al reported that highfat diet behaviour could form atherosclerotic plaque and block blood vessels by damaging vascular endothelium and, thereafter, contribute to hypertension and other cardiovascular and cerebrovascular diseases by lumen narrowing (36) . In addition, high-salt diets can promote body fluid volume expansion, adrenal cortical production and release of sodium pump inhibitor increasing through inhibiting the cell membrane Na + 2K + 2ATP enzyme activity, which could contribute to blood pressure elevation and dyslipidaemia (37) .…”
Section: Main Findingsmentioning
confidence: 99%
“…Lactoferrin receptors (low-density lipoprotein receptor-related protein 1 and 2, intelectin 1 and nucleolin) are localised on a variety of cells such as monocytes, lymphocytes, adipocytes, hepatocytes and endothelial cells [4]. So far, multiple activities of lactoferrin have been shown in both preclinical [5,6,7] and clinical studies [8,9]. It was documented that lactoferrin possesses anti-inflammatory, antibacterial, antiviral, immunomodulatory, antioxidant, and anticancer activities [4].…”
Section: Introductionmentioning
confidence: 99%
“… Biological functions of bioactive milk osteopontin. Related references cited in the Figure: ( a: [ 125 , 126 ]; b : [ 127 ]; c : [ 128 ]; d : [ 129 ]; e : [ 130 , 131 , 132 ]; f : [ 133 ]; g : [ 134 ]; h : [ 135 ]; i : [ 136 ]; j : [ 137 ]; k : [ 138 ]; l : [ 139 , 140 ]; m : [ 141 ]; n : [ 142 ]; o : [ 143 ]; p : [ 144 ]; q : [ 145 ]; r : [ 146 ]; s : [ 147 ]; t : [ 148 , 149 ]; u : [ 150 ]). …”
Section: Figureunclassified